COVID-19 and Sick Leave: An Analysis of the Ibermutua Cohort of Over 1,651,305 Spanish Workers in the First Trimester of 2020 - Calvo-Bonacho, Eva; Catalina-Romero, Carlos; Fernández-Labandera, Carlos; Fernández-Meseguer, Ana; González-Quintela, Arturo; Martínez-Muñoz, Paloma; Quevedo, Luis; Valdivielso, Pedro; Sánchez-Chaparro, Miguel Ángel (Frontiers in Public Health, 2020)
Objectives: The worldwide SARS-COV2 pandemic has impacted the health of workers and companies. The aim is to quantify it according to sick leave. Methods Using ICD-9 codes, we analysed Ibermutua records of all sick leaves during the first trimester of 2020, compared to during the same months of 2017, 2018, and 2019. We stratified the analysis by causes, patient sex, activity sectors, and regional data. All sick leaves were adjusted by the number of Ibermutua-affiliated persons in each period. Results: In March 2020, there was an unprecedented (116%) increase in total sick leaves, mainly due to infectious and respiratory diseases. Men and women were equally affected. All activity sectors were impacted, with the highest increase (457%) observed among health-related workers, especially due to contagious disease. The incidences of sick leaves were heterogeneous among different regions. Cost-analysis of sick leaves during the first trimester of 2020 compared with in previous years showed 40.3 % increment (mean 2,813 € vs 2,005 € per 100 affiliated workers). Conclusions: The SARS-COV2 pandemic is having a huge impact on workers’ health, as shown by data regarding sick leaves in March 2020. This is associated with greater economic burden for companies, both due to the cost associated with sick leaves and the losses in productivity due to confinement.